2020
DOI: 10.1093/ofid/ofaa439.301
|View full text |Cite
|
Sign up to set email alerts
|

257. Staphylococcus aureus Bacteremia: Does Intravenous Drug Use Impact Quality of Care and Clinical Outcomes?

Abstract: Background Individuals with intravenous drug use (IDU) have higher risk for Staphylococcus aureus bacteremia (SAB) and increased management complexity. The goal of this study was to compare differences in SAB characteristics, adherence to standard of care metrics, and clinical outcomes in those with and without IDU. Methods A retrospective chart review was conducted on cases of SAB between January 1, 2016 and December 31, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…PWID were more likely to have endocarditis, SSTI, and pneumonia, consistent with single-center studies [ 18 , 19 ]. For example, McClellan et al reported that, among hospitalized patients with SAB, PWID had higher rates of IE (31.4% vs 8.5%, P < .001) and of SSTI (25.7% vs 14.8%, P = .02) than non-PWID [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…PWID were more likely to have endocarditis, SSTI, and pneumonia, consistent with single-center studies [ 18 , 19 ]. For example, McClellan et al reported that, among hospitalized patients with SAB, PWID had higher rates of IE (31.4% vs 8.5%, P < .001) and of SSTI (25.7% vs 14.8%, P = .02) than non-PWID [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…The age of PWID in this study was younger than non-PWID patients, consistent with a median age of 41 years (IQR, 36–48 years) for the PWID population in England [ 6 , 34 ]. This may account for the lower prevalence of medical comorbidities observed among PWID, as has been reported previously [ 19 ]. Diabetes, HIV, CKD, and malignancy have been associated with increased risk of recurrent infection and death following SAB [ 12 , 13 , 33 ].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations